2014
DOI: 10.1186/preaccept-1223313303133840
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of a foreign protein from budding yeasts is enhanced by cotranslational translocation and by suppression of vacuolar targeting

Abstract: Background: Budding yeasts are often used to secrete foreign proteins, but the efficiency is variable. To identify roadblocks in the yeast secretory pathway, we used a monomeric superfolder GFP (msGFP) as a visual tracer in Saccharomyces cerevisiae and Pichia pastoris. Results: One roadblock for msGFP secretion is translocation into the ER. Foreign proteins are typically fused to the bipartite α-factor secretion signal, which consists of the signal sequence followed by the pro region. The α-factor signal seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…Indeed, a clear CSE4 homolog on chromosome two (2011 genome location 1026080..1026598 or 2016 genome location 1026960..1027478) was present on Chr2. P. pastoris Cse4 was tagged with the monomeric superfolder GFP variant msGFP (Fitzgerald and Glick, 2014). For visualizing nuclei, the cells also expressed ER-targeted DsRed-HDEL, which fills the nuclear envelope with red fluorescence (Bevis et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a clear CSE4 homolog on chromosome two (2011 genome location 1026080..1026598 or 2016 genome location 1026960..1027478) was present on Chr2. P. pastoris Cse4 was tagged with the monomeric superfolder GFP variant msGFP (Fitzgerald and Glick, 2014). For visualizing nuclei, the cells also expressed ER-targeted DsRed-HDEL, which fills the nuclear envelope with red fluorescence (Bevis et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…To label Cse4, PPY12 genomic DNA was used as a PCR template to amplify the CSE4 gene, including 589 bp of upstream sequence and 294 bp of downstream sequence, and this fragment was inserted into the polylinker of a pUC19 derivative containing the Saccharomyces cerevisiae ARG4 gene (Rossanese et al, 1999). In-Fusion cloning was then used to generate a chimeric gene encoding msGFP (Fitzgerald and Glick, 2014) fused to the C-terminus of Cse4 with an intervening GSSGSSGSSGSS linker. This construct was linearized with SpeI for integration at the CSE4 locus, resulting in a tandem duplication of CSE4 in which one copy of the gene was fused to msGFP.…”
Section: Methodsmentioning
confidence: 99%
“…To create the HLA-F 293T construct, β 2 m-HLA-F was modified via the addition of the native HLA-F signal peptide (MAPRSLLLLLSGALALTDTWA) followed by a Gly-Ser linker (GSGSSGSSGSSGSS), msGFP (MDSTESLFTGVVPILVELDGDVNGHKFSVRGEGEGDATNGKLTLKFICTTGKLPVPWPTLVTTLTYGVQCFSRYPDHMKQHDFFKSAMPEGYVQERTITFKDDGTYKTRAEVKFEGDTLVNRIELKGIDFKEDGNILGHKLEYNFNSHNVYITADKQKNGIKANFKIRHNVEDGSVQLADHYQQNTPIGDGPVLLPDNHYLSTQSKLSKDPNEKRDHMVLLEFVTAAGITH) (Fitzgerald and Glick, 2014) and a C-terminal 8x his-tag. A similar construct containing a 3C protease site downstream of the msGFP and a C-terminal Avitag upstream of a 3C protease site and 8x his-tag was created for production of HLA-F 293T tetramers.…”
Section: Star Methodsmentioning
confidence: 99%
“…for human serum albumin (HSA), human lysozyme, some fungal enzymes -see Gasser et al 2013). Earlier this year, two publications employing signal sequences only (Fitzgerald & Glick, 2014;Govindappa et al, 2014), as well as a mutant version of MFa (Lin-Cereghino et al, 2013), have been reported. Reasons for differences in secretion rates are manifold, but processing of the secretion leader, thermodynamic instability, misfolding, as well as misdirecting, are obvious; however, not yet understood in full detail.…”
Section: Introductionmentioning
confidence: 99%